Encumbered estates court, Ireland, 1848-1849 - Lane, PG (Economic & Social Studies, 1972)
This study presents an account of the ;background of conditions in Ireland's thought, and legislative measures, to the establishment of an encumbered estates court in 1849.
Keywords: Encumbered Estates; Ireland